2022
DOI: 10.2196/33941
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Between Tweet Numbers and Over-the-counter Drug Sales for Allergic Rhinitis: Retrospective Analysis

Abstract: Background Health-related social media data are increasingly being used in disease surveillance studies. In particular, surveillance of infectious diseases such as influenza has demonstrated high correlations between the number of social media posts mentioning the disease and the number of patients who went to the hospital and were diagnosed with the disease. However, the prevalence of some diseases, such as allergic rhinitis, cannot be estimated based on the number of patients alone. Specifically,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Not only infectious diseases but also hay fever has been reported correlation ( r = 0.97) in the UK [ 41 ]. In Japan’s case, tweets related to allergic rhinitis were highly correlated ( r = 0.84) with their drug sales [ 42 ]. We reached similar results using longer-term data.…”
Section: Discussionmentioning
confidence: 99%
“…Not only infectious diseases but also hay fever has been reported correlation ( r = 0.97) in the UK [ 41 ]. In Japan’s case, tweets related to allergic rhinitis were highly correlated ( r = 0.84) with their drug sales [ 42 ]. We reached similar results using longer-term data.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent clinical context, SM was analyzed to assess the international incidence of COVID‐19 infection and infection‐related deaths amongst otolaryngologists 74 . Six studies specifically examined the use of Tweet patterns to trend pollen counts and assess correlation with rates of allergic rhinitis 3,32,33,42,53,86 . Wakamiya et al found the number of Tweets including the keywords “allergic rhinitis” to be positively correlated with the number of patient visits during the main seasonal allergic rhinitis phase 33 .…”
Section: Discussionmentioning
confidence: 99%
“…74 Six studies specifically examined the use of Tweet patterns to trend pollen counts and assess correlation with rates of allergic rhinitis. 3,32,33,42,53,86 Wakamiya et al found the number of Tweets including the keywords "allergic rhinitis" to be positively correlated with the number of patient visits during the main seasonal allergic rhinitis phase. 33 Overall, studies analyzing these platforms can gain potentially useful data to map spatiotemporal trends of environmental forces.…”
Section: Trainee Educationmentioning
confidence: 99%